2020
DOI: 10.1111/bph.14992
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection in right heart failure

Abstract: Ischaemic and pharmacological conditioning of the left ventricle is mediated by the activation of signalling cascades, which finally converge at the mitochondria and reduce ischaemia/reperfusion (I/R) injury. Whereas the molecular mechanisms of conditioning in the left ventricle are well characterized, cardioprotection of the right ventricle is principally feasible but less established. Similar to what is known for the left ventricle, a dysregulation in signalling pathways seems to play a role in I/R injury of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 157 publications
(323 reference statements)
1
6
0
Order By: Relevance
“…In contrast to the right ventricle, the relevance of MAO-A inhibition for left ventricular pressure overload–induced heart failure and other left ventricular pathologies was previously shown in various experimental models ( 10 ). This study thus fills the gap between the right and left ventricles and provides more evidence that the right and left heart respond differently to pressure overload, as suggested by previous studies regarding the source of ROS and antioxidant defense mechanisms in right and left heart hypertrophy and failure ( 2 , 11 , 12 ). Moreover, this study adds another piece to the puzzle to understand the multifactorial pathogenesis of PH, and it supports previous findings that increased ROS contribute to pulmonary vascular remodeling.…”
supporting
confidence: 74%
“…In contrast to the right ventricle, the relevance of MAO-A inhibition for left ventricular pressure overload–induced heart failure and other left ventricular pathologies was previously shown in various experimental models ( 10 ). This study thus fills the gap between the right and left ventricles and provides more evidence that the right and left heart respond differently to pressure overload, as suggested by previous studies regarding the source of ROS and antioxidant defense mechanisms in right and left heart hypertrophy and failure ( 2 , 11 , 12 ). Moreover, this study adds another piece to the puzzle to understand the multifactorial pathogenesis of PH, and it supports previous findings that increased ROS contribute to pulmonary vascular remodeling.…”
supporting
confidence: 74%
“…There are now thousands of studies which reported >100 different signaling molecules and mechanisms of conditioning in a wide range of experimental preparations, from isolated subcellular structures to isolated cardiomyocytes with exposure to hypoxia/reoxygenation, from cultured cardiomyoblast cell lines to freshly isolated neonatal or adult cardiomyocytes, from buffer-perfused isolated hearts with global or regional ischemia and reperfusion to in vivo and in situ preparations with coronary artery occlusion and reperfusion, using different methodologies from biochemical to immunoblotting techniques [ 42 ]. Intensive research has been performed to elucidate the signalling pathways, which become activated upon a conditioning stimulus [ 43 ]. The protein kinase B, endothelial nitric oxygen synthase, glycogen synthase kinase 3b, p44/42, and signal transducer and activator of transcription 3 may be considered as indicators of the intracellular changes taking place during remote ischemic conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…4 ). 44 , 45 Mitophagy regulates both mitochondrial quantity and quality in vivo in response to hypoxia or hypoxic conditions especially I/R heart injury in both platelets and cardiomyocytes. It was further suggested that monitoring mitochondrial quality and mitochondrial functional status of platelets offered useful and convenient approach before the application of ischemic and pharmacological preconditioning, providing a new strategy to protect cardiac function and fight cardiovascular diseases.…”
Section: Fundc1 In Diseasesmentioning
confidence: 99%